Clinical and statistical analysis of predictors oflethal outcomes in tuberculosis patients treated in medical units of the Russian Federal penitentiary system - M. E. Vostroknutov; S. A. Sterlikov; V. G. Kudrina; N. M. Popova (Туберкулез и болезни лёгких)
The objective: to determine risk factors of lethal outcomes (predictors) in tuberculosis patients treated with chemotherapy regimens I, II, III during conﬁnement in the Russian penitentiary system.Subjects and Methods: data on 6,069 patients registered for treatment in 2019 and 2020 were studied. Univariate and multivariate analyses were performed.Results. The following factors were found to have eﬀect on mortality: age (aOR = 1.05; 95% CI 1.03-1.06), multiple localizations of tuberculosis (aOR = 11.08; 95% CI 5.12-24.20), concurrent HIV infection (aOR = 9.13; 95% CI 6.90-12.24), and positive sputum microscopy at registration (aOR = 5.18; 95% CI 3.93-6.81). The patient gender was found to have no eﬀect (OR = 0.9; 95% CI 0.4-1.9; p = 1).